Consumer's characteristics of yogurt in Manado, North Sulawesi - Indonesia - Wantasen, E.; Elly, F. H.; Santa, N. M. (Diponegoro University, 2017)
The objective of this study was to analyze consumer’s characteristics of yogurt as one of fermented dairy product, consumers satisfaction and factors influencing consumers purchase decision on yogurt in Manado city. The primary data were collected using structured questionnaire from a total sample of 400 consumers in Manado City. Samples were selected using the accidental sampling method with schedule (using alternating date/ day and place, respectively). Collecting data were done from July to September 2015. The result indicated that most consumers were teenagers, female students, and single persons. Consumers of yogurt in Manado City are were categorized quite satisfied with yogurt product. The product availability had to be considered by producer in order to increase consumer satisfaction. Partially, factors that significantly influencing consumer’s purchase decision in Manado were preservative content, product availability, variant flavor, product volume and additional nutritive value.